2006
DOI: 10.1111/j.1742-4658.2006.05242.x
|View full text |Cite
|
Sign up to set email alerts
|

IPSE/alpha‐1, a major secretory glycoprotein antigen from schistosome eggs, expresses the Lewis X motif on core‐difucosylated N‐glycans

Abstract: Schistosomes are parasitic flatworms that infect millions of people in (sub)tropical areas around the world. Glycoconjugates of schistosomes play a critical role in the interaction of the different developmental stages of the parasite with the host. In particular, glycosylated components of the eggs produced by the adult worm pairs living in the bloodstream are strongly immunogenic. We have investigated the glycosylation of interleukin‐4‐inducing factor from schistosome eggs (IPSE/alpha‐1), a major secretory e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
77
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 80 publications
(81 citation statements)
references
References 45 publications
(76 reference statements)
4
77
0
Order By: Relevance
“…However, the results also indicate that deletion of the C terminus, including the NLS, abrogates this function. As an explanation for this, our recent studies have shown that dimerization of native IPSE/alpha-1 requires a cysteine residue (C132) at the C terminus of IPSE, which forms an interchain disulfide bond (54). This cysteine is removed in IPSE/alpha-1 ⌬NLS but is present in the IPSE/ alpha-1 3R mutant.…”
Section: Translocation Of Ipse/alpha-1 To the Nucleus Requires A C-tementioning
confidence: 98%
See 2 more Smart Citations
“…However, the results also indicate that deletion of the C terminus, including the NLS, abrogates this function. As an explanation for this, our recent studies have shown that dimerization of native IPSE/alpha-1 requires a cysteine residue (C132) at the C terminus of IPSE, which forms an interchain disulfide bond (54). This cysteine is removed in IPSE/alpha-1 ⌬NLS but is present in the IPSE/ alpha-1 3R mutant.…”
Section: Translocation Of Ipse/alpha-1 To the Nucleus Requires A C-tementioning
confidence: 98%
“…Native IPSE/alpha-1 released by schistosome eggs is a dimer as a consequence of an interchain disulfide bond involving the C-terminal cysteine residue C132 (54). Despite the relatively low molecular mass (33 to 35 kDa) of IPSE/alpha-1 dimers, the mutants defective for NLS activity were excluded from the nucleus (Fig.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…LC fractions were analyzed by matrix-assisted laser desorption ionization-time of flight mass spectrometry (MALDI-TOF MS) using Ultraflex II and Ultraflextreme mass spectrometers (Bruker Daltonics, Bremen, Germany) in negative-ion reflectron mode with 2,5-dihydroxybenzoic acid (DHB) (Bruker Daltonics) as the matrix. The detected masses were translated into putative glycan structures using Glycopeakfinder (http://glyco -peakfinder.org), the literature (9,(19)(20)(21)(22)(23)(24)(25)(26)(27)(36)(37)(38)(39)(40)(41), and our own unpublished tandem-MS (MS-MS) data. The three most abundant signals in each mass spectrum were translated into glycan structures, unless the individual signals made up less than 10% of the total intensity of all glycan masses in the spectrum of a glycan sample.…”
Section: Methodsmentioning
confidence: 99%
“…Several approaches have become commonly used to address this issue: (i) analysis of the N-linked carbohydrates released from the protein by enzymatic procedures followed by derivatization of the glycan pool [14], or (ii) analysis of the glycopeptides formed by proteolytic degradation of the protein [15,16]. While the former provides a global picture of the glycans decorating the protein, the second strategy discloses information about the carbohydrate attachment site, which can be obtained using various tandem mass spectrometric methods (reviewed in [17]).…”
Section: Introductionmentioning
confidence: 99%